Does Treatment Order Matter? Investigating the Ability of Bacteriophage to Augment Antibiotic Activity against Staphylococcus aureus Biofilms - Kumaran, Dilini; Taha, Mariam; Yi, QiLong; Ramirez-Arcos, Sandra; Diallo, Jean-Simon; Carli, Alberto; Abdelbary, Hesham (Frontiers in Microbiology, 2018)
The inability to effectively treat biofilm-related infections is a major clinical challenge. This has been attributed to the heightened antibiotic tolerance conferred to bacterial cells embedded within biofilms. Lytic bacteriophages (phages) have evolved to effectively infect and eradicate biofilm-associated cells. The current study was designed to investigate the ability of phage treatment to enhance the activity of antibiotics against biofilm-forming Staphylococcus aureus. The biofilm positive S. aureus strain ATCC 35556, the lytic S. aureus phage SATA-8505, and five antibiotics (cefazolin, vancomycin, dicloxacillin, tetracycline, and linezolid), used to treat S. aureus infections, were tested in this study. The ability of the SATA-8505 phage to augment the effect of these antibiotics against biofilm-associated S. aureus cells was assessed by exposing them to one of the five following treatment strategies: (i) antibiotics alone, (ii) phage alone, (iii) a combination of the two treatments simultaneously, (iv) staggered exposure to the phage followed by antibiotics, and (v) staggered exposure to antibiotics followed by exposure to phage. The effect of each treatment strategy on biofilm cells was assessed by enumerating viable bacterial cells. The results demonstrate that the treatment of biofilms with either SATA-8505, antibiotics, or both simultaneously resulted in minimal reduction of viable biofilm-associated cells. However, a significant reduction [up to 3 log colony forming unit (CFU)/mL] was observed when the phage treatment preceded antibiotics. This effect was most pronounced with vancomycin and cefazolin which exhibited synergistic interactions with SATA-8505, particularly at lower antibiotic concentrations. This in vitro study provides proof of principle for the ability of phages to augment the activity of antibiotics against S. aureus biofilms. Our results also demonstrate that therapeutic outcomes can be influenced by the sequence in which these therapeutic agents are administered, and the nature of their interactions. Further investigation into the interactions between lytic phages and antibiotics against various biofilm-forming organisms is important to direct future clinical translation of efficacious antibiotic–phage combination therapeutic strategies.